Static disorder and local structure in zinc(II) isonicotinate, a quartzlike metal-organic framework - Collings, I; Tucker, MG; Keen, D; Goodwin, A (2012)
Using a combination of Rietveld and reverse Monte Carlo (RMC) refinement of neutron total scattering data, we find that the 10 K structure of zinc(II) isonicotinate shows strong evidence of static disorder. This disorder takes the form of transverse displacements of the isonicotinate ligand and results in elongated atomic displacement parameters and dampening of the experimental G(r). We analyse the RMC configurations using an approach derived from geometric algebra. Complications regarding the inclusion of hydrogenous guest molecules within the pore structure are discussed. This study highlights the way in which structural flexibility can give rise to multiple lowenergy ground states in metal-organic framework materials. © by Oldenbourg Wissenschaftsverlag, München.